Applying ground gas and gas flux monitoring techniques to low-enthalpy, shallow geothermal energy exploration. (December 2021) - Smith, Douglas; Taylor-Curran, Helen; Barkwith, Andrew; Lister, Thomas, R.; Kirk, Karen; Hannis, Sarah; Shorter, Kirsty; Walker-Verkuil, Kyle
Highlights: Ground gas sampling methods applied to a complex industrial site intended for low-enthalpy, shallow geothermal energy research. Interpretation of concentrations and fluxes of CO2 and CH4 and concentrations of N2, O2, H2 S and H2 and stable isotopes of carbon in CO2 . Comparison with other background gas studies. Evaluation of the benefits and limitations of background gas and process-based approaches for pre-operational gas studies. Abstract: Ground gas and gas flux testing has been undertaken in a variety of situations including detecting volcanic and geothermal activity and monitoring landfill and carbon storage. However, there are no documented studies of its application to shallow geothermal investigations, particularly where the water in disused mines will be used as the conduit for heat and the overlying ground has a complex industrial heritage. Background ground gas and gas flux measurements from three separate campaigns at a mine water heat research site in Glasgow, UK did not reveal any concerns regarding mine gas or other potentially harmful gases from previous land uses. The detected CO2 was found to be predominantly of biological origin and reflected the expected quantities based upon land use, seasonal and weather fluctuations and was consistent with other UK sites. One location is recommended for further investigation due to higher-than-expected nitrogen and lower oxygen measurements. Some hydrogen gas was detected, albeit well below explosive limits, which may be present as a result of past industrial site uses, highlighting the need for more investigation into the presence of hydrogen at ex-industrial sites. Apart from this there was very little evidence of the industrial site history in the gas characterisation. A process-based analysis, based upon the stoichiometric relationship of CO2, CH4, O2 and N2, was applied to the results. This complemented, but was not a substitute for, the background survey. There were limitations with the process-based approach when there was not a clear anomalous CO2 signal or where potentially more than one process was occurring simultaneously.